Motivational cherry picking - Tobias Regner; Gerhard Riener (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
We construct a simple three person trust game with one trustor and two trustees. The trustor has the possibility to either trust both trustees or none, while the trustees make their decisions either sequentially or simultaneously, depending on the treatment. When trustees play sequentially, follower trustees who are informed about the leader's choice are significantly less kind than in the simultaneous move treatment as well as the leader trustees. These findings can not be explained by models of inequity aversion, pure guilt aversion, or conformity. Instead, follower trustees cherry pick the motivation that serves them best. When the leader trustee played unkind, they tend to conform and play unkind, too. When the leader made a kind choice, followers seem to perceive the duty of reciprocating to the trustor as already fulfilled by the leader. While guilt works well as a motivational force in a dyadic situation, it gets alleviated easily when there is someone to shift responsibility to, like the leader in our three person game.
Keywords: D03; D71; C79; C92; 330; team production; trust; principal agent; guilt; guilt alleviation; conformity; false consensus effect; lab experiment; cherry picking; Arbeitsgruppe; Prinzipal-Agent-Theorie; Vertrauen; Spieltheorie; Test